2018
DOI: 10.1007/s10549-018-4861-4
|View full text |Cite
|
Sign up to set email alerts
|

Availability of prior mammograms affects incomplete report rates in mobile screening mammography

Abstract: Incomplete reports were more frequent in mobile mammography than the fixed site. The availability of prior comparison mammograms at time of interpretation decreased the rate of incomplete mammogram reports. Recall rates were higher without prior comparison mammograms and lowest when comparison FFDM mammograms were available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“… Manitoba Diabetes Integration Project (DIP) People with diabetes residing in 19 First Nation reserves in Manitoba PoC laboratory tests, nurse assessment and diabetes management and education advice Directed by members from tribal councils Descriptive quantitative analysis of key evaluation indicators [ 79 ] Patient records with diabetes ( n = 2790) between 2008 and 2013 Multiple outcomes including patient mean avoided cost ($272,289 per year) and change in mean difference of clinical indicators of diabetes: mass − 0.4 kg, HbA1c − 0.09%, systolic blood pressure − 1.6 mmHg, diastolic blood pressure − 1.0 mmHg, MAP −1.1 mmHg, LDL 0.09 mmol/L Health Canada and Aboriginal Diabetes Initiative Mobile Diabetes Telemedicine Clinic (MDTC) People with diabetes residing in 59 First Nations communities in Northern British Columbia Diabetes screening and management including eye exam, point of care (PoC) testing, nursing and dietitian assessments and education Delivered by First Nations health service Longitudinal cohort data analysis [ 79 , 87 ] Patient records from 2003 to 2009 Modest improvements in some clinical outcomes (e.g. mean decline in body mass of 1.6 kg, mean decline in LDL was 0.3 mmol/L, mean absolute decline in A1c was 0.4%) Health Canada and Aboriginal Diabetes Initiative Great Plains Mobile Mammography Screening Native American and Alaskan women Mammography screening and referrals to tertiary centers Delivered by Indian health services (1) Retrospective analysis of clinic records [ 89 ] (2) Retrospective analysis of clinical records [ 90 ] (1) Native Indian and Alaskan Native patient records 2007–2009 ( n = 2640) (2) Complete patient records from 2007 to 2009 ( n = 1771) (1) Incomplete patient reports were more frequent in mobile mammography than the fixed site (21.9% v. 15.2%) (2) Adherence to screening guidelines found in 39.86% of patients Not reported Tuba City Regional Health Care Corporation Mobile Health Program Native Indian people from Navajo, Hopi and San Juan Southern Paiute tribes Primary Healthcare including immunizations and dental exams Delivered by an Indian Tribal Organisation None to report None to report None to report Health Resources and Services Administration (Grant) Winslow Indian Health Care Centre Medical Mobile Vehicle Native Indian people Primary care, dental, pharmacy, public health nursing, physi...…”
Section: Resultsmentioning
confidence: 99%
“… Manitoba Diabetes Integration Project (DIP) People with diabetes residing in 19 First Nation reserves in Manitoba PoC laboratory tests, nurse assessment and diabetes management and education advice Directed by members from tribal councils Descriptive quantitative analysis of key evaluation indicators [ 79 ] Patient records with diabetes ( n = 2790) between 2008 and 2013 Multiple outcomes including patient mean avoided cost ($272,289 per year) and change in mean difference of clinical indicators of diabetes: mass − 0.4 kg, HbA1c − 0.09%, systolic blood pressure − 1.6 mmHg, diastolic blood pressure − 1.0 mmHg, MAP −1.1 mmHg, LDL 0.09 mmol/L Health Canada and Aboriginal Diabetes Initiative Mobile Diabetes Telemedicine Clinic (MDTC) People with diabetes residing in 59 First Nations communities in Northern British Columbia Diabetes screening and management including eye exam, point of care (PoC) testing, nursing and dietitian assessments and education Delivered by First Nations health service Longitudinal cohort data analysis [ 79 , 87 ] Patient records from 2003 to 2009 Modest improvements in some clinical outcomes (e.g. mean decline in body mass of 1.6 kg, mean decline in LDL was 0.3 mmol/L, mean absolute decline in A1c was 0.4%) Health Canada and Aboriginal Diabetes Initiative Great Plains Mobile Mammography Screening Native American and Alaskan women Mammography screening and referrals to tertiary centers Delivered by Indian health services (1) Retrospective analysis of clinic records [ 89 ] (2) Retrospective analysis of clinical records [ 90 ] (1) Native Indian and Alaskan Native patient records 2007–2009 ( n = 2640) (2) Complete patient records from 2007 to 2009 ( n = 1771) (1) Incomplete patient reports were more frequent in mobile mammography than the fixed site (21.9% v. 15.2%) (2) Adherence to screening guidelines found in 39.86% of patients Not reported Tuba City Regional Health Care Corporation Mobile Health Program Native Indian people from Navajo, Hopi and San Juan Southern Paiute tribes Primary Healthcare including immunizations and dental exams Delivered by an Indian Tribal Organisation None to report None to report None to report Health Resources and Services Administration (Grant) Winslow Indian Health Care Centre Medical Mobile Vehicle Native Indian people Primary care, dental, pharmacy, public health nursing, physi...…”
Section: Resultsmentioning
confidence: 99%
“…We did not include women with personal histories of breast cancer because diagnostic views were often performed during the screening examination, and we could not determine if these diagnostic views were part of surveillance imaging or for the evaluation of a new finding. Although prior research has shown higher recall rates when comparison images are unavailable to the reading radiologist [ 38 ], most facilities in the BCSC do not provide data on comparison image availability. However, among subsequent screening examinations with complete information on comparison images, only 0.8% indicated no comparison films.…”
Section: Discussionmentioning
confidence: 99%